"Dilute-and-Shoot" Rapid-Separation Liquid Chromatography Tandem Mass Spectrometry Method for Fast Detection of Thiodiglycolic Acid in Urine. Issue 5 (October 2015) - Baygildiev, Timur; Braun, Arcady; Stavrianidi, Andrey; Rodin, Igor; Shpigun, Oleg; Rybalchenko, Igor; Ananieva, Irina
A new sensitive rapid-separation liquid chromatography tandem mass spectrometry approach for the determination of thiodiglycolic acid (TDGA) in urine has been developed. The use of the "dilute-and-shoot" method helps to shorten the sample preparation stage and provides a sensitive and direct approach for TDGA determination in urine. Chromatographic separation of the analyte and other urine compounds was achieved using a reverse-phase liquid chromatography column with mobile phases consisting of 0.1% formic acid in water and acetonitrile in a gradient elution mode. For the identification and quantification of TDGA electrospray ionization-tandem mass spectrometry monitoring, two precursor-to-product ion transitions were used. The method demonstrates good linearity and has a detection limit of 50 ng mL −1 in urine.